Genetic susceptibility to allergic bronchopulmonary aspergillosis in asthma: a genetic association study. Issue 1 (December 2016) - Overton, Nicola; Denning, David; Bowyer, Paul; Simpson, Angela
Abstract Background In patients with asthma, the fungusAspergillus fumigatus can cause allergic bronchopulmonary aspergillosis (ABPA). Familial ABPA is reported, and some genetic factors have been associated with the disease, however, these are small studies (n ≤ 38) and do not explain all cases of ABPA. Methods We analysed SNPs in 95 ABPA patients, comparing frequencies to 152 atopic asthmatic and 279 healthy controls. Twenty two genes were selected from literature, and 195 tagging SNPs were analysed for genetic association with ABPA using logistic regression corrected for multiple testing. We also analysed monocyte-derived macrophage gene expression before and during co-culture withA. fumigatus . Results Seventeen ABPA-associated SNPs (ABPA v Atopic asthma) were identified. Three remained significant after correction for multiple testing; IL13 rs20541, IL4R rs3024656, TLR3 rs1879026. We also identified minor differences in macrophage gene expression responses in the ABPA group compared to the control groups. Conclusions Multiple SNPs are now associated with ABPA. Some are novel associations. These associations implicate cytokine pathways and receptors in the aberrant response toA. fumigatus and susceptibility to ABPA, providing insights into the pathogenesis of ABPA and/or its complications. We hope these results will lead to increased understanding and improved treatment and diagnostics for ABPA.